EFEKTIVITAS PENERAPAN UNDANG-UNDANG NOMOR 24 TAHUN 2011 TENTANG BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN DI RUMAH SAKIT UMUM DAERAH ATAMBUA - Talo, Gramelia Sannyta; Asnawi, Norani; Nuban, Detji Kory Elianor Rooselved (Petitum Law Journal, 2024)
The Social Security Administering Body (BPJS) is a legal entity formed to administer the National Health Insurance Program (JKN). This is a form of the government's commitment to the Implementation of National Social Security in article 5 paragraph (1) that "the Social Security Administering Body must be established by law -Invite”. Currently, the implementation of Law Number 24 of 2011 concerning the Social Security Administering Body at the Atambua Regional General Hospital has not been carried out effectively because its role in health services at the Atambua Regional General Hospital is not yet clear. This research is empirical juridical legal research. This research is descriptive in nature and analyzes primary data to determine the effectiveness of the implementation of Law Number 24 of 2011 concerning the Health Social Security Administering Body (BPJS) at the Atambua Regional General Hospital. Data collection uses observation, documentation and interview techniques. The results of the research show that: (1) The implementation of Law Number 24 of 2011 concerning the Health Social Security Administering Body (BPJS) at the Atambua Regional General Hospital has not been effective and (2) The influencing factors include internal factors (communication and resources human) and external factors (BPJS Health contribution collection, availability of health facilities and participant registration process).